Interesses e critérios : as escolhas do leitor - Barbosa, Aline Ramos (2017)
Considering that subjectivity is a little discussed aspect in academic researches that deal with reading, this work has as its central objective to analyze how it – the subjectivity – is presented in the dissertations defended by the master's degree students linked to the Postgraduate Program in Letters from Federal University of Sergipe in the period between 2010 and 2016. For this, we use a bibliography that discusses, above all, the reading process and the questions related to the reader. In order to achieve this goal, we have brought to the center of the discussion some positions and concepts of Compagnon (1999; 2009), showing that the literature occupies a place that is much more encompassing than it is imagined and all questioning that permeates it; Candido (1988, 2006), who helps us to understand literature from a more social perspective; Todorov (2010), making us think about the literature itself and what it represents for society; Bloom (2001), who focuses more on the process of literary reading, since, for him, reading presents us unimaginable worlds. In addition to the citations of these theorists, which appears with more recurrence in the body of the text, we also list some positions of Iser (1979) and Jauss (1999). They are responsible for the Aesthetics of Reception, current of thought quite pertinent for the reader's appreciation. In addition, Jouve (2012), Rouxel (2013) and Langlade (2013) bring discussions about the subjective character of literary reading. To encompass other aspects concerning the figure of the reader, we use the assumptions brought by Eagleton (2006), Eco (1988), Culler (1997) and Barthes (2008).